2008
DOI: 10.1210/er.2007-0039
|View full text |Cite
|
Sign up to set email alerts
|

The Unfolded Protein Response: A Pathway That Links Insulin Demand with β-Cell Failure and Diabetes

Abstract: The endoplasmic reticulum (ER) is the entry site into the secretory pathway for newly synthesized proteins destined for the cell surface or released into the extracellular milieu. The study of protein folding and trafficking within the ER is an extremely active area of research that has provided novel insights into many disease processes. Cells have evolved mechanisms to modulate the capacity and quality of the ER protein-folding machinery to prevent the accumulation of unfolded or misfolded proteins. These si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
444
2
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 496 publications
(469 citation statements)
references
References 168 publications
6
444
2
9
Order By: Relevance
“…The life-long stimulus for the beta cell to secrete large amounts of insulin for maintaining euglycaemia is associated with an increased protein-folding burden in the ER. This may lead to accumulation of misfolded proteins, most importantly proinsulin, resulting in ER stress [54,55]. This, together with oxidative stress elicited by excessive mitochondrial generation of reactive oxygen species, leads to beta cell dysfunction [56,57].…”
Section: Autophagy In Beta Cell Physiology and Diabetesmentioning
confidence: 99%
“…The life-long stimulus for the beta cell to secrete large amounts of insulin for maintaining euglycaemia is associated with an increased protein-folding burden in the ER. This may lead to accumulation of misfolded proteins, most importantly proinsulin, resulting in ER stress [54,55]. This, together with oxidative stress elicited by excessive mitochondrial generation of reactive oxygen species, leads to beta cell dysfunction [56,57].…”
Section: Autophagy In Beta Cell Physiology and Diabetesmentioning
confidence: 99%
“…ER stress is induced under conditions such as overload of protein synthesis/processing, accumulation of structurally abnormal proteins, disturbance of post-translational modification and ER calcium homeostasis abnormalities. When ER stress develops, cells respond by unfolded protein response (UPR), facilitating protein folding via the induction of chaperone proteins, attenuation of translations, as well as degradation of misfolded proteins, a process called ERassociated degradation [23][24][25]. If the stress is severe, apoptosis is induced.…”
Section: Introductionmentioning
confidence: 99%
“…11,23 Numerous studies have suggested that ER stress signaling pathways are implicated in various diseases, including atherosclerosis, metabolic disease, liver disease, and inflammatory bowel disease. 6,[24][25][26][27] However, whether HIV PI-induced apoptosis is also associated with the activation of the ER stress response in IECs has not been explored. Herein, we describe our investigation of whether HIV PI-induced activation of the ER stress response is involved in the induction of apoptosis and disruption of normal intestinal barrier function both in in vitro cell culture models and in in vivo mice models.…”
Section: Discussionmentioning
confidence: 99%